Commercial valved spacers versus home-made spacers for delivering bronchodilator therapy in pediatric acute asthma: a cost-effectiveness analysis (2020)
Objective: Although valved spacers are the preferred method for administering metered-dose inhaler bronchodilators such as albuterol in pediatric acute asthma, their high cost and their lack of availability have limited their use, especially in low- and middle-income countries (LMICs). Because of this, it is a common practice to use home-made spacers, although a formal analysis evaluating their cost-effectiveness is lacking. Therefore, the objective of this study was to analyze the cost-effectiveness of home-made spacers compared to commercial valved spacers for delivering bronchodilator therapy in pediatric acute asthma. Methods: A decision-analysis model was used to estimate health outcomes and costs of a simulated cohort of pediatric patients treated for acute asthma. Effectiveness parameters were obtained from a systematic review of the literature. Cost data were obtained from hospital bills and from the national manual of drug prices in Colombia. The study was carried out from the perspective of the national healthcare system in Colombia, a middle-income country (MIC). The main outcome of the model was avoidance of hospital admission. Results: Base-case analysis showed that compared to commercial valved spacers, administering bronchodilators with home-made spacers results in lower overall treatment costs (US$126.75 vs. US$128.59 average cost per patient) without a significant difference in the probability of hospitalization avoided (0.8500 vs. 0.8500). Conclusions: The present study shows that in Colombia, an MIC, compared with commercial valved spacers, the use of home-made spacers for administering bronchodilator therapy is more cost-effective because it yields a similar probability of hospital admission at lower overall treatment costs.